Pengaruh Segmentasi, Targeting Dan Positioning Terhadap Keputusan Pembelian Produk Overtoun - Ramadhani, Muhammad Ivan Arthana; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research was conducted to determine the analysis of marketing strategies at Overtoun in the form of segmentation, targeting, positioning and their influence on consumer purchasing decisions. This research is a type of explanatory research with a quantitative approach, which was carried out to test the influence between variables. The population in this research are all consumers who have used or are currently using Overtoun products in the Gadang Village area. From this population, a sample will be determined using Malhotra's formula method so that a sample of 100 samples will be obtained. Data analysis in this research consists of instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination testing. The results of this research show that based on the results of the t test, there is a partial influence between the segmentation, targeting and positioning variables on consumer purchasing decision variables. Adjusted R Square of 64.2% of the dependent variable, namely the decision to take credit, can be explained by the variables. Segmentation (X1), Targeting (X2), Positioning (X3) while 35.8% is explained by other variables outside the research model. Keywords: Consumer Purchasing Decisions, Segmentation, Targeting, Positioning